Hope for the separated : wounded marriages can be healed - Chapman, Gary D., 1938- (Chicago : Moody Publishers, 2005)
You may not feel like reconciling. You may not see hope for a reunion. But the biblical ideal for a separated couple is reconciliation. So how do you do it? When doors slam and angry words fly, when things just aren't working out, and even when your spouse is interested in someone else, there is hope. Dr. Gary Chapman will show you that by following the proven advice of God's Word you can achieve reconciliation with your mate.
What happened to our dream? -- Taking constructive action -- Self-development during separation -- Developing your relationship with God -- Developing your relationship with your mate -- Long-distance love -- Tough love -- How will I handle the loneliness? -- What about my bitterness? -- If your spouse returns -- If your spouse demands a divorce -- Facing the future.
Includes bibliographical references.
Keywords: Divorce -- Religious aspects -- Christianity; Marriage -- Religious aspects -- Christianity; Reconciliation -- Religious aspects -- Christianity; Separated people